Formulation and Constraints of Women Economic Empowerment of AN-Nisa’ Cooperative - Daris Zunaida; Rini Rahayu Kurniati; Sri Nuringwahyu (Universitas Muhammadiyah Ponorogo, 2019)
One of the problems faced by Muslim women in Indonesia is the lack of empowerment in the economic field. An-Nisa’ cooperative in Pati district, Central Java is one of the cooperative which consists of women who want to empower women. The effort to empower women’s economy is certainly not easy because of the gender stigma in women and also the effort of male gender domination of women. This research uses qualitative research method with descriptive approach. The study was conducted for 6 months in An-Nisa’ cooperative. The research data were collected through in-depth interview, observation, documentation and Focus Group Discussion (FGD). The results show that the economic empowerment effort undertaken by An-Nisa’ cooperative through the agreement that all members are women. Empowerment is also done through unsecured loands. Constraints faced in the economic empowerment of women is the domination of husbands in the utilization of productive credit